The procedure of complex technical assessment of the ancient building described on the example of the vicarage building in Wojsławice - Banaszak, Justyna; Halicka, Anna (Budownictwo i Architektura / Civil and Architectural Engineering, 2011)
In this article procedure and methodology of preparing the technical assessment of the ancient building are presented. This procedure was implemented in testing of old destroyed vicarage building in Wojslawice. The results of tests are described. On the basis of these results the conclusions concerning the causes of damages are formulated. The methods of repair of building are proposed.